Rancang Bangun Sistem Kontrol Tangan Menggunakan Motor Servo dan Sensor AD8232 Untuk Memudahkan Penyandag Disabilitas Prostetik - Aprilianto, Sandi; Mulyadi, Adi; Suryadhianto, Untung (CV. Sekawan Siji, 2025)
Prosthetic disability is a concern for Indonesian society. Based on data from the Ministry of Social Affairs for 2020-2024, people with disabilities reached 22.97 million people, with physical disabilities being the largest category. Therefore, research is proposed to address prosthetic disability with a hand design and control system similar to a natural hand. The design uses fiber, resin, and catalysts. Meanwhile, a control system is used to regulate the movement of the prosthetic fingers based on angular variations in the servo motor. The resulting prosthetic hand design is divided into 15 segments, such as the thumb, the other four fingers, and the palm. Then, the control system produces stable finger movements with a 0° angle control for opening the hand, holding a glass with a 70°–87° angle control, and a full grip with a 140°–168° angle control. The purpose of implementing this technology is to create more effective and responsive solutions to improve the independence and quality of life for individuals with physical disabilities.